2019
DOI: 10.1016/j.ejca.2019.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Pooled Analysis of external-beam RADiotherapy parameters in phase II and phase III trials in radiochemotherapy in Anal Cancer (PARADAC)

Abstract: Acknowledgments of research support for the study: The Kom Op Tegen Kanker supported the development of this project through the "Emmanuel van der Schueren Fellowship for Quality Assurance in Radiotherapy" EORTC fellow grants (Oscar Matzinger, Melissa Christiaens). UK Coordinating Committee for Cancer Research (UKCCCR), Radiation Therapy Oncology Group (RTOG), French Federation Nationale des Centres de Lutte Contre le Cancer (FNLCC), European Organization for the Research and Treatment of Cancer (EORTC) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Likewise, delays/reductions and omissions of the second cycle of chemotherapy led to poorer PFS (hazard ratio 1.56 and 2.39, respectively) and OS (hazard ratio 1.92 and 2.88, respectively). These data were confirmed by a pooled analysis of individual patient data from seven phase II/III trials, in which longer overall treatment time led to higher rates of loco-regional failure, recurrence and death [27]. The prognostic importance of treatment compliance has also been reported in real-world populations.…”
Section: Recent Studies On Localised Anal Squamous Cell Carcinomamentioning
confidence: 65%
See 1 more Smart Citation
“…Likewise, delays/reductions and omissions of the second cycle of chemotherapy led to poorer PFS (hazard ratio 1.56 and 2.39, respectively) and OS (hazard ratio 1.92 and 2.88, respectively). These data were confirmed by a pooled analysis of individual patient data from seven phase II/III trials, in which longer overall treatment time led to higher rates of loco-regional failure, recurrence and death [27]. The prognostic importance of treatment compliance has also been reported in real-world populations.…”
Section: Recent Studies On Localised Anal Squamous Cell Carcinomamentioning
confidence: 65%
“…New treatment options will hopefully become available in the near future for both localised and advanced ASCC. [27]. The prognostic importance of treatment compliance has also been reported in real-world populations.…”
Section: Key Pointsmentioning
confidence: 94%
“…However, it highlights an important message that avoiding as much treatment interruptions as possible and reducing their duration seem to improve the patients’ outcome, pauses being increasingly questioned [ 29 ]. As a matter of fact, in a recent pooled analysis, shorter overall treatment time was associated with longer PFS [ 30 ]. Finally, a significant proportion of patients who entered in this model received an experimental drug (panitumumab) not standardly used, but this was taken into account in the model and did not seem to interfere with the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This allows for the reduction of acute toxicity, mainly in the perineal skin area, therefore a break in irradiation caused by skin radiation reaction is currently very rare. Studies have shown that interruptions in treatment reduce the effectiveness of local radiotherapy, so they should be avoided or shortened whenever possible [8]. Depending on the stage the most frequently used doses are 50-60…”
Section: Principles Of Radiation Therapymentioning
confidence: 99%